Sistem Pendukung Keputusan Mengidentifikasi Faktor Ketidakaktifan Siswa dalam Pembelajaran Menggunakan Metode AHP pada SMK Bina Satria Medan - Ulhar, Lukna Aulia; Khairul Ummi (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
SMK Bina Satria Medan faces challenges in addressing the low level of student participation during the learning process, which directly affects academic achievement and their readiness to enter the workforce. One of the main obstacles encountered by the school is the absence of a structured system to analyze the factors contributing to student inactivity. Until now, the identification process has been conducted manually through teacher observations and subjective assessments, resulting in analyses that are often inaccurate and difficult to use as a basis for strategic decision-making. To address this issue, this study focuses on developing a Decision Support System (DSS) designed to assist the school in evaluating and determining the level of influence of various factors that contribute to student inactivity more objectively. The system assesses multiple aspects, including internal factors—such as motivation, learning interest, and discipline—as well as external factors, such as family support, economic conditions, and social environment. The Analytic Hierarchy Process (AHP) method is applied to weight and perform pairwise comparisons among criteria in order to determine the priority level of each contributing factor. Through the implementation of this system, the school is expected to obtain accurate and targeted recommendations for designing effective intervention strategies, such as strengthening counseling programs, enhancing student motivation, or innovating teaching methods. In this way, the DSS can play a significant role in improving student participation and supporting a more optimal and productive learning process.